A search for new γ-ray blazars from infrared selected candidates. Issue Volume 15:Issue S356(2019) (October 2019) - Musiimenta, Blessing; Sversut Arsioli, Bruno; Jurua, Edward; Mutabazi, Tom
Abstract: We present a systematic study of gamma-ray blazar candidates based on a sample of 40 objects taken from the WIBR catalogue. By using a likelihood analysis, 26 of the 40 sources showed significant gamma-ray signatures ⩾ 3 σ . Using high-energy test statistics (TS) maps, we confirm 8 sources, which are completely new, and show another 15 promising γ -ray candidates. The results from this analysis show that a multi-frequency approach can help to improve the current description of the gamma-ray sky.